THE ROLE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Davlatova Durdona; Berdikulova Mahbuba (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Artificial Intelligence (AI) is rapidly transforming the global education system by introducing innovative tools that enhance teaching and learning processes. From personalized learning platforms to intelligent tutoring systems, AI is reshaping how students access knowledge and how teachers deliver instruction. This article examines the role of AI in education, supported by real-life examples and statistical evidence, while also discussing its challenges and future implications.